2006
DOI: 10.1016/j.bmc.2006.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative structure–activity relationships of benztropine analogues at the dopamine transporter and histamine H1 receptors

Abstract: Benztropine (BZT) and its analogues inhibit dopamine uptake and bind with moderate to high affinity to the dopamine transporter (DAT). However, many of these compounds, in contrast to other monoamine uptake inhibitors, lack cocaine-like behavioral effects and fail to potentiate the effects of cocaine. The BZT analogues also exhibit varied binding affinities for muscarinic M 1 and histamine H 1 receptors. In this study a comparative analysis was conducted of pharmacophoric features with respect to the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The greatest effect of cyproheptadine on soman-induced seizures is likely due to its anticholinergic properties. Anticholinergic properties are well-studied and therapeutically used properties of first generation antihistamines (Niemegeers et al, 1982, Graudins et al, 1998, Kulkarni et al, 2006. A previous study compared anticholinergic properties of 10 different antihistamines and found that cyproheptadine had the most potent anticholinergic properties (Kubo et al, 1987, Orzechowski et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest effect of cyproheptadine on soman-induced seizures is likely due to its anticholinergic properties. Anticholinergic properties are well-studied and therapeutically used properties of first generation antihistamines (Niemegeers et al, 1982, Graudins et al, 1998, Kulkarni et al, 2006. A previous study compared anticholinergic properties of 10 different antihistamines and found that cyproheptadine had the most potent anticholinergic properties (Kubo et al, 1987, Orzechowski et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have failed to correlate muscarinic receptor binding with the benztropines' lack of cocaine-like effects [73,74]. It should also be noted that several of these analogues demonstrated high to moderate affinity for histamine H1 receptors [75,76]. However, a relationship between H1 binding profiles and their behavioral actions was not demonstrated [76].…”
Section: Sar Studies With Benztropine Analogsmentioning
confidence: 99%
“…In humans, benztropine's effects are similar to those of the prototypic anticholinergic, atropine, while exhibiting histamine H1 antagonism similar to pyrilamine maleate (Esplin, 1970;Physicians Desk Reference, 2005). Recently, benztropine and related tropane analogs have been evaluated in preclinical studies for their inhibitory effects on the DAT (Dar et al, 2005;Desai et al, 2005a;Kulkarni et al, 2004Kulkarni et al, , 2006Reith et al, 2001;Ukario et al, 2005). Kulkarni et al's (2004) study showed that N-substituted analogs inhibited dopamine uptake and that this function was positively correlated with DAT binding affinities.…”
Section: Introductionmentioning
confidence: 97%